Efektifitas Model Pembelajaran Pendidikan Agama Islam Berbasis Living Values Education (LVE) dalam Meningkatkan Wawasan Kejujuran Siswa - Dewi Sinta; Saepul Anwar; Munawar Rahmat; Abid Nurhuda; Inamul Hasan Ansori (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyse the effectiveness of the Living Values Education (LVE)-based Islamic Religious Education (IRE) learning model in improving the honesty awareness of junior high school students. The background of this study stems from the problem of IRE learning, which tends to be cognitively oriented and has not been optimal in internalising the value of honesty as the foundation of Islamic character. This study used a quantitative approach with a pretest–posttest non-equivalent control group quasi-experimental design. The research subjects were eighth-grade students at a private junior high school in Bandung, divided into an experimental class and a control class. The research instrument was an honesty awareness test that had been tested for validity and reliability. Data analysis was conducted using independent sample t-tests, paired sample t-tests, and N-Gain tests to measure the level of treatment effectiveness. The results showed a significant difference in the increase in honesty insight between the experimental class and the control class after treatment. The experimental class that implemented the LVE model experienced a higher average score increase and was in the ‘quite effective’ effectiveness category, compared to the control class, which was classified as ‘less effective’. These findings confirm that the integration of values through the LVE approach is able to strengthen the internalisation of honesty in a more meaningful way in PAI learning. This study contributes to the development of PAI learning.